2022
DOI: 10.3389/fmars.2022.920082
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effect of Acetone Extracts from Microalgae Chlorella sp. WZ13 on RAW264.7 Cells and TPA-induced Ear Edema in Mice

Abstract: Microalgae extracts have a wide range of uses in the field of healthcare and nutrition. However, the use of microalgae extracts in anti-inflammatory properties and their mechanism of action have not yet been fully studied. Here, we show that extracts from Chlorella sp. WZ13 (CSE-WZ13) dose-dependently reduced nitrite production, inhibited the expression of inducible nitric oxide synthase (iNOS) protein, and decreased the production of the gene and inflammatory cytokines tumor necrosis factor-α (TNF-α) and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…On the other hand, Chlorella genus is a widely studied microalga for its application in industries such as animal nutrition, pharmaceuticals, and health [6,40,41]. We have previously reported that cells treated with C. sorokiniana metabolites caused a significant reduction in rotavirus infectivity [5].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Chlorella genus is a widely studied microalga for its application in industries such as animal nutrition, pharmaceuticals, and health [6,40,41]. We have previously reported that cells treated with C. sorokiniana metabolites caused a significant reduction in rotavirus infectivity [5].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the molecular docking study revealed the powerful binding of ChV bioactive compounds to the binding sites of IL1RAP, IL6RA, TNFRSF1A, and TRAF1 in quails. Accumulating evidence indicates that ChV’s potential to mitigate inflammation is ascribed to its abundance in PUFA, which plays a crucial role in regulating the release of pro-inflammatory cytokines and relieving cellular inflammation ( Abdelnour et al, 2019a ; Remize et al, 2021 ; Yang et al, 2022 ). This is in agreement with Abdelhamid et al (2020) who reported that ChV supplementation contributed to the downregulation of TNF-α in splenic fish.…”
Section: Discussionmentioning
confidence: 99%